INCREASING PRODUCTION CAPACITY AND DIVERSIFICATION OF TRADITIONAL BEVERAGE PRODUCTS "KUNYIT ASEM" AT WEDANG MANDIRI BUSINESS GROUP IN LANGSA CITY - T. Putri Lindung Bulan; Tuti Meutia; Mulia Syafrida Sari (Global Science Society, 2022)
This community service activity was carried out at Gampong Jawa, Langsa Baro District, Langsa City which aims to overcome the problems faced by partners who are MSME entrepreneurs who run a traditional beverage production business in the form of 'kunyit tamarind'. Businesses run by partners have the prospect of developing better by considering the opportunities and potential they have. The method used in implementing this service are (1) the lecture and discussion method; namely by formulating and justifying partner problems to provide the best solution; (2) Demonstration and practice methods, namely modifying production equipment and improving production systems in order to obtain optimal results, and (3) Observation methods, namely monitoring and assisting partners' businesses during the PkM implementation. Efforts to increase production capacity are carried out by adding additional supporting production machines such as automatic grating machines, so as to help production efficiency, by saving the number of production hours. Furthermore, improvements are given to the appearance of the packaging and brand to make it more attractive, and influence buying interest in customers. Product diversification is done by increasing the variety of bottle packaging sizes with adjusted prices.